Inverse Chirality Probe in Poly(3‐alkylthiophene) Derivative. Issue 7 (2nd February 2015) - Destri, Silvia; Barba, Luisa; Gelmetti, Ilario; Di Bari, Lorenzo; Porzio, William
<x xml:space="preserve">Abstract</x> The preparation and study of a new poly(3‐alkyloxythiophene)—bearing a chiral center—is presented, with particular reference to the evolution of optical activity in passing from solution to solid state. The combination of optical analysis, electronic circular dichroism, and X‐ray diffraction of powders or films supplies strong indications of a possible use of this material as an inverse chiral probe.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>